The challenges of literacy, inclusion, and public trust in the digital Islamic banking ecosystem: An urban context study in Indonesia - Hasan, Hurriah Ali; Razaq, Abd Rahim; Sa'aid, Hafizah Besar (Journal of Islamic Economics Lariba, 2026)
IntroductionThe development of Islamic banking in Indonesia shows great potential, but still faces literacy constraints, public trust, and low inclusion. The public understands the basic principles of Islamic banking but has not mastered the technical aspects of operations. Digital transformation, which is supposed to expand access to Islamic financial institutions, has not been optimally utilized due to informational barriers, risk perception, and quality of digital services.ObjectivesThis study aims to analyze the relationship between Islamic banking literacy, trust, and inclusion, identify the main obstacles in the use of digital services of Islamic financial institutions, and formulate strategies that can break the cycle of problems related to low public understanding and participation. The study also evaluates how education, transparency, and digital innovation can increase engagement in Islamic banking.MethodThis study uses a descriptive quantitative approach with a cross-sectional design. Data was obtained through a structured questionnaire to 198 respondents in Makassar City. Descriptive statistical analysis is used to describe literacy, trust, and inclusion levels, as well as identify patterns of structural, informational, and perceptual barriers in the use of Islamic banking services, especially digital-based ones..ResultsThe results show that public literacy is still at the level of basic and general understanding, public trust is low due to lack of transparency, while inclusion is hampered by lack of information, limited digital infrastructure, and negative perceptions. The adoption of sharia digital technology is very low despite the high ownership of smartphones. Key barriers include awareness, risk perception, and the quality of the app's user experience.ImplicationsThese findings confirm the need for strategies to improve operational literacy, institutional transparency, and digital innovation based on user needs. Strengthening regulations, optimizing the role of the Sharia Supervisory Board (Dewan Pengawas Syariah - DPS), and collaboration with fintech can increase trust and inclusion. The results of the research provide more effective policy direction and service design to accelerate the transformation of Islamic banking.Originality/NoveltyThis research offers a new perspective by integrating three variables—literacy, trust, and inclusion—in the digitalization of Islamic banking. The study highlights digital barriers from a user experience perspective, not just technology access. This approach results in innovative recommendations based on transparency, user experience, and more applicable educational strategies.